Macroporous pyrene tetraketone-triazine covalent organic framework material as well as synthesis method and application thereof

Modifying the lithium-sulfur battery separator with macroporous pyrene-tetraone-triazine covalent organic framework material solved the problems of polysulfide shuttle effect and lithium dendrite growth in lithium-sulfur batteries, and improved the electrochemical kinetics and cycle stability of the battery.

CN121495066APending Publication Date: 2026-02-10BEIJING INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511577128.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-31
Publication Date
2026-02-10

AI Technical Summary

Technical Problem

Problems such as polysulfide shuttle effect, lithium dendrite growth, and slow electrochemical kinetics in lithium-sulfur batteries lead to unstable battery performance and shortened cycle life.

Method used

A macroporous pyrene-tetraone-triazine covalent organic framework material (TTB-PTO-COF) was synthesized via a Schiff base reaction. It has an ordered pore structure and abundant redox active sites, and can be used to modify lithium-sulfur battery separators to adsorb LiPS and catalyze LiPS conversion, while inhibiting lithium dendrite growth.

Benefits of technology

It improves the cycle stability and rate performance of lithium-sulfur batteries, especially under high sulfur loading and low electrolyte conditions, and improves electrochemical kinetics and overall battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121495066A_ABST
    Figure CN121495066A_ABST
Patent Text Reader

Abstract

The invention relates to a macroporous pyrene tetraketone-triazine covalent organic framework material as well as a synthesis method and application thereof, and belongs to the technical field of organic functional materials. The material is prepared from 2, 7-aminopyrene-4, 5, 9, 10-tetraketone and 4, 4 ', 4' '-(1, 3, 5-triazine-2, 4, 6-triyl) tri (benzaldehyde) through polymerization. The material has a relatively large mesoporous structure, high crystallinity and rich redox active sites. The large-size mesoporous structure is favorable for keeping relatively high ion flux of the diaphragm, the bidirectional catalytic action of pyrene tetraketone conjugated carbonyl can improve the reaction kinetics of the high-load lithium-sulfur battery, and the soft-package lithium-sulfur battery prepared under the conditions of high-activity load and poor electrolyte shows stable cycle performance and relatively high specific capacity.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a kind of macroporous pyrromethene-tetrazine covalent organic framework material, synthesis method and its application, belong to organic functional material technical field. BACKGROUND

[0002] Lithium-sulfur batteries have rapidly grown in demand for energy storage solutions as the world transitions to low-carbon and renewable energy systems. Lithium-sulfur (Li-S) batteries are a promising energy storage technology due to their exceptional theoretical energy density (2600 Wh kg -1 ) and specific capacity (1672 mAh g -1 ). However, despite these attractive features, Li-S batteries still face several key issues in practical applications, limiting their widespread commercialization. Polysulfide shuttle effect: One of the most significant challenges in Li-S batteries is the shuttle effect caused by soluble lithium polysulfides (LiPSs, such as Li2S4 and Li2S6). These intermediates are highly mobile, leading to the dissolution and redistribution of LiPS between the anode and cathode, resulting in poor coulombic efficiency, capacity fading, and reduced cycle stability. The polysulfide shuttle effect is a major obstacle limiting the performance of Li-S batteries; Inhomogeneous lithium deposition and lithium dendrite growth: The anode of Li-S batteries is typically made of lithium metal, which is prone to form lithium dendrites during cycling, which can cause safety issues such as short circuits and shorten battery life. The formation of dendrites also exacerbates the instability of the solid-state electrolyte interface (SEI) layer, which is crucial for protecting the lithium metal anode; Low conductivity of sulfur: Sulfur, as the cathode material in Li-S batteries, has poor electrical conductivity, leading to ineffective utilization of sulfur for high-capacity storage and fast discharge rates. This results in poor electrochemical performance of the battery, reducing overall efficiency; Volume expansion: Lithium sulfide (Li2S) is the final discharge product in Li-S batteries, which causes about 80% volume change during charge and discharge due to its low density. This volume expansion can damage the cathode structure and lead to poor mechanical integrity, which in turn affects cycle stability.

[0003] To address these issues, the most common solution is to modify the separator, which is the key component responsible for separating the anode and cathode and allowing the transport of ions in the electrolyte. Some existing methods for modifying the separator include: polysulfide adsorbing materials: previous studies have used carbon-based materials, metal oxides, and organic polymers to adsorb LiPS, inhibiting their shuttle effect. However, although these materials can adsorb LiPS to some extent, they often cannot maintain sufficient stability over a long period of time, and their performance may decline after multiple cycles; electrolyte modification: some studies have explored the addition of additives to the electrolyte to inhibit the shuttle effect, but this method has a problem in that a large amount of additives is required, which increases the cost and complexity of the battery system; dendrite inhibition strategies: although some separators and solid electrolyte interface (SEI) layers can reduce the formation of dendrites, most materials have not been able to achieve uniform lithium deposition under high current cycling conditions. Based on the shortcomings of existing technologies, there is an urgent need to develop a new separator modification material that can effectively inhibit the shuttle effect of polysulfides, improve electrochemical kinetics, inhibit dendrite growth, and enhance the overall stability and performance of Li-S batteries. SUMMARY

[0004] The present application aims to overcome the shortcomings of the prior art and provide a macroporous pyrromethene-triazine covalent organic framework material, a synthesis method and applications thereof. The material solves the problems of polysulfide shuttle effect, lithium dendrite growth, and slow electrochemical kinetics in Li-S batteries. The material is obtained by polymerization of 2,7-amino pyrromethene-4,5,9,10-tetraone (PTO-NH2) and 4,4',4''-(1,3,5-triazine-2,4,6-triazyl)tris(benzaldehyde) (TTB). By incorporating a covalent organic framework (COF) material with redox active sites into the design, the material can effectively chemisorb and immobilize lithium polysulfides (LiPS), preventing their diffusion and improving battery performance. At the same time, the TTB-PTO-COF material acts as a redox medium through its rich redox active groups (such as carbonyl and imine functional groups), promoting the conversion of LiPS and improving the electrochemical kinetics and sulfur utilization efficiency of the battery. In addition, the ordered pore structure of the TTB-PTO-COF material regulates lithium ion flow and inhibits lithium dendrite growth, thereby improving the long-term stability of the lithium metal anode. The material also has a high specific surface area, large pores, and bidirectional catalytic function, greatly improving the cycle stability and rate performance of Li-S batteries, especially under high sulfur loading and low electrolyte conditions.

[0005] To achieve the above-mentioned purposes, the technical solutions of the present application are as follows.

[0006] A macroporous pyrromethene-triazine covalent organic framework material, the material having a basic structural unit as shown below: .

[0007] Preferably, the material has an ordered crystalline structure, a specific surface area of 200-400 m 2 / g, and a pore size of 3.5-4 nm.

[0008] A preparation method of the macroporous pyrromethene-triazine covalent organic framework material according to the present application, the method steps comprising: Under a protective gas atmosphere, 2,7-aminopyrromethene-4,5,9,10-tetraone and 4,4',4''-(1,3,5-triazine-2,4,6-triazyl)tris(benzaldehyde) are polymerized by Schiff base reaction to obtain the macroporous pyrromethene-triazine covalent organic framework material.

[0009] Preferably, under a protective gas atmosphere, 2,7-aminopyrromethene-4,5,9,10-tetraone, 4,4',4''-(1,3,5-triazine-2,4,6-triazyl)tris(benzaldehyde), solvent and catalyst are mixed, and then the mixture is subjected to cyclic liquid nitrogen flash-pumping-extraction-thawing, and then the mixture is reacted at 80-150℃ for more than 24h in a sealed reaction container. After the reaction is completed, the macroporous pyrromethene-triazine covalent organic framework material is obtained by filtration, washing, purification and drying.

[0010] Preferably, the molar ratio of 2,7-aminopyrromethene-4,5,9,10-tetraone to 4,4',4''-(1,3,5-triazine-2,4,6-triazyl)tris(benzaldehyde) is 3-4:2.

[0011] Preferably, the solvent comprises one or more of N,N-dimethylacetamide, N,N-dimethylformamide, mesitylene and 1.4-dioxane.

[0012] Preferably, the catalyst comprises acetic acid, hydrochloric acid and trifluoroacetic acid.

[0013] Preferably, the reaction temperature is 100-120℃, and the reaction time is 24-120h.

[0014] The macroporous pyrromethene-triazine covalent organic framework material according to the present application is used as a modification material to prepare a modified lithium-sulfur battery separator.

[0015] Preferably, the macroporous pyrromethene-triazine covalent organic framework material, a conductive agent and a binder are uniformly mixed to obtain a slurry, and the slurry is coated on the separator and dried to obtain the modified lithium-sulfur battery separator.

[0016] Preferably, the mass ratio of the macroporous pyrromethene-triazine covalent organic framework material, the conductive agent and the binder is 5:4:1-8:1:1.

[0017] Preferably, the thickness of the modification material is 1-20 µm.

[0018] Preferably, the conductive agent includes carbon black, Ketjen black, acetylene black, and carbon nanotubes; the binder includes polyvinylidene fluoride (PVDF), sodium alginate, polyethylene dioxythiophene (PEDOT), and polydopamine (PDA); and the separator includes Celgard 2320, Celgard 2325, Celgard 2400, Celgard 2500, and Celgard 2501.

[0019] A lithium-sulfur battery, wherein the separator of the battery is the modified lithium-sulfur battery separator described in this invention, and the modifying material is located on the positive electrode side.

[0020] Beneficial effects This invention provides a macroporous pyrene-tetrone-triazine covalent organic framework material, which possesses a large mesoporous structure, high crystallinity, and abundant redox active sites. The large-size mesoporous structure is beneficial for maintaining a high ion flux of the membrane, and the bidirectional catalytic effect of the conjugated carbonyl group of pyrene-tetrone can improve the reaction kinetics of high-load lithium-sulfur batteries. The pouch lithium-sulfur battery prepared under high-activity loading and low electrolyte conditions exhibits stable cycle performance and high specific capacity.

[0021] This invention provides a method for preparing macroporous pyrene-tetraone-triazine covalent organic framework materials. The method uses 2,7-aminopyrene-4,5,9,10-tetraone and 4,4',4''-(1,3,5-triazine-2,4,6-triyl)tris(benzaldehyde) as monomers, synthesized via a Schiff base reaction. The method is simple to operate and easily industrialized.

[0022] This invention provides an application of a macroporous pyrenetetrone-triazine covalent organic framework material as a lithium-sulfur battery separator modification material. It can effectively adsorb soluble LiPS generated at the positive electrode and inhibit the growth of lithium dendrites at the negative electrode, while catalyzing the conversion of sulfides, thus synergistically improving the electrochemical performance of lithium-sulfur batteries. Attached Figure Description

[0023] Figures 1a-1c The NMR spectra of compounds I, II, and III are shown below.

[0024] Figures 2a-2e The structural characterization diagrams of compound IV are shown below, including infrared spectroscopy, thermogravimetric analysis, powder XRD, nitrogen adsorption-desorption isotherms, scanning electron microscopy, and high-resolution transmission electron microscopy.

[0025] Figure 3 UV-vis spectra of Li2S6 solution before and after adsorption with carbon black CB and TTB-PTO-COF (inset: optical photograph).

[0026] Figures 4a-4bOptical photographs and scanning electron microscope images of the TTB-PTO-COF modified diaphragm material.

[0027] Figure 4c For CB@2500 and COF@2500 at 0.2 mV s -1 CV curves at scan rate.

[0028] Figure 5 COF@2500 and CB@2500 modified separators were used in Li || Li symmetric cells ranging from 0.2 to 8.0 mA cm⁻¹. -2 Rate performance at current density.

[0029] Figure 6a Half-cells assembled with COF@2500 and CB@2500 modified separators at 0.1 mV s -1 The cyclic voltammetry curve.

[0030] Figure 6b Charge-discharge curves of half-cells assembled with COF@2500 and CB@2500 modified separators at 0.2C.

[0031] Figure 6c EIS curves of half-cells assembled with COF@2500 and modified separators.

[0032] Figure 6d Long-cycle curves of half-cells assembled with COF@2500 and CB@2500 modified separators at 2C current density.

[0033] Figure 6e Cycling curves of high-sulfur surface-loaded half-cells assembled with COF@2500 and CB@2500 modified separators at 0.1C. Detailed Implementation

[0034] The present invention will be further described in detail below with reference to specific embodiments.

[0035] Example 1 The preparation method of 2,7-aminopyrene-4,5,9,10-tetraone includes the following steps: 1) Synthesis of pyrene-4,5,9,10-tetraone: Pyrene reacts with sodium periodate and ruthenium chloride to form pyrene-4,5,9,10-tetraone(II); according to literature: Chem. Eng. J ., 2024, 489 , 151103. Figure 1a The 1H NMR spectrum of pyrene-4,5,9,10-tetraone is shown. 1H NMR (400 MHz, CDCl3, ppm): δ 8.33 (d, 4H), 7.73 (t, 2H) ppm.

[0036] 2) Synthesis of 2,7-nitropyrene-4,5,9,10-tetraone (PTO-NO2): According to the literature: Angew. Chem. Int. Ed. 2024, 63, e202409421.

[0037] 3) Weigh 2.0 g (7.6 mmol) of pyrene-4,5,9,10-tetraone into a 250 mL round-bottom flask containing 40 mL of 98% sulfuric acid. Then, add 10 mL of nitric acid dropwise to the mixture in an ice bath. Heat the mixture at 90 °C for 12 hours. Subsequently, pour the reaction mixture into an ice-water mixture (800 mL). Collect the resulting yellow precipitate, filter, wash with plenty of water, and dry under reduced pressure at 80 °C to give a bright yellow solid. Figure 1b The 1H NMR spectrum of 2,7-nitropyrene-4,5,9,10-tetraone is shown. 1 H NMR (400 MHz, DMSO- d 6,ppm): δ 8.90 (s, 4H).

[0038] 4) Synthesis of 2,7-aminopyrene-4,5,9,10-tetraone (PTO-NH2): According to the literature: Angew. Chem. Int. Ed. 2024, 63, e202409421.

[0039] PTO-NO2 (1.0 g, 2.85 mmol) was placed in a 100 mL round-bottom flask, and acetic acid (10.0 mL) and concentrated hydrochloric acid (10.0 mL) were added to form a yellow suspension. Stannous chloride dihydrate (SnCl2·2H2O, 7.5 g, 33.8 mmol) was then slowly added, and the mixture was heated at 45 °C for 1 hour. A gray solid was obtained by filtration and dried under vacuum at 80 °C. The resulting gray solid (2.83 g) was then suspended in anhydrous methanol (40 mL) with 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (2.83 g, 1.3 mmol) and stirred at 40 °C for 24 hours under argon protection. The reaction mixture was diluted with ethyl acetate (250 mL), and the dark purple precipitate was collected by filtration, washed thoroughly with ethyl acetate, and dried under vacuum at 80 °C. The resulting product was used directly without further purification. Figure 1c The 1H NMR spectrum of 2,7-aminopyrene-4,5,9,10-tetraone is shown. 1 H NMR (400 MHz, DMSO- d6, ppm): δ 7.29 (s, 4H), 5.90 (s, 4H).

[0040] The reaction formula is as follows:

[0041] Formula (I) Formula (II) Formula (III) Example 2 A method for preparing organic framework compound (Ⅳ) based on the polymerization of 2,7-aminopyrene-4,5,9,10-tetraone (PTO-NH2) and 4,4',4''-(1,3,5-triazine-2,4,6-triyl)tris(benzaldehyde) (TTB) includes the following steps: PTO-NH2 (26.4 mg, 0.09 mmol) and TTB (22.0 mg, 0.06 mmol) were added to a mixed solvent containing dimethylacetamide (DMAc, 0.75 mL), mesitylene (Mes, 0.25 mL), and 6 M aqueous acetic acid (0.1 mL). Ampoules were flash-frozen in a liquid nitrogen bath and sealed after three vacuum cycles. The ampoules were then heated to room temperature and placed in a 120°C oven for 5 days. After cooling to room temperature, the precipitate was collected by filtration and washed three times each with anhydrous DMF, ethanol, and dichloromethane (DCM). The product was further purified by Soxhlet extraction with tetrahydrofuran (THF) for 24 hours and finally dried under vacuum at 120°C for 12 hours to obtain a brown powder, named TTB-PTO-COF.

[0042] The reaction formula is as follows:

[0043] Formula (Ⅳ) Appendix Figure 2a The FT-IR spectrum of TTB-PTO-COF powder prepared in Example 2 shows that the disappearance of the amino peak indicates successful polymerization. (See attached image.) Figure 2b The FT-IR thermogravimetric analysis curves of TTB-PTO-COF powder prepared in Example 2 demonstrate that the TTB-PTO-COF material possesses good thermal stability. (See attached image.) Figure 2c The powder XRD diffraction pattern of TTB-PTO-COF powder prepared in Example 2 shows a good match between the measured and simulated diffraction peaks, indicating that TTB-PTO-COF is a two-dimensional covalent organic framework material with good crystallinity and phase purity; (See attached image) Figure 2d The nitrogen adsorption-desorption isotherm curves of TTB-PTO-COF powder indicate that the material has a good specific surface area and porosity. Figure 2eScanning electron microscope (SEM) and high-resolution transmission electron microscope (HRTEM) images of the TTB-PTO-COF powder prepared in Example 2 are shown. TTB-PTO-COF exhibits a rod-like morphology at the micrometer scale. The corresponding elemental distribution map shows that C, N, and O elements are uniformly distributed in the TTB-PTO-COF material. Furthermore, clear lattice fringes can be observed in the HRTEM images, with a lattice spacing of 0.34 nm, corresponding to the (001) crystal plane of TTB-PTO-COF, indicating that the TTB-PTO-COF material has high crystallinity and ordered pores.

[0044] Example 3 The adsorption performance test of TTB-PTO-COF and carbon black materials for polysulfides includes the following steps: In a glove box, 10 mg of TTB-PTO-COF and 10 mg of carbon black were added to 1 mL of 10 mM Li2S6 solution to conduct LiPS adsorption experiments.

[0045] Figure 3 The images show optical photographs and UV absorption spectra of the adsorption experiment, demonstrating that the TTB-PTO-COF material exhibits a stronger adsorption capacity for Li2S6 compared to carbon black.

[0046] Example 4 The preparation methods for modified separators based on TTB-PTO-COF material and control group carbon black modified separators include the following steps: 70 mg of carbon black (Carbon Black CB) or 70 mg of TTB-PTO-COF material, 20 mg of carbon black, and 10 mg of PVDF were mixed and milled for 45 minutes. The homogeneous mixture was then dispersed in 0.5 mL of NMP and milled for another hour. The resulting slurry was coated onto a diaphragm (Celgard 2500) using a doctor blade and vacuum-dried overnight at 60°C. Finally, the coated diaphragm was cut into discs with a diameter of 16 mm. The loading of TTB-PTO-COF material was approximately 0.40 mg cm⁻¹. -2 The modified membrane materials are designated as CB@2500 and COF@2500, respectively.

[0047] Appendix Figure 4a Optical photographs of the TTB-PTO-COF modified diaphragm (COF@2500) in Example 4 are attached. Figure 4b The image shows a scanning transmission electron microscope (STEM) image of the TTB-PTO-COF modified diaphragm (COF@2500) from Example 4, indicating its thickness of 5 μm. (See attached image.) Figure 4cThe CV curve of the battery assembled with the TTB-PTO-COF modified separator showed two pairs of redox peaks (2.81 / 2.72 V and 2.59 / 2.41 V) within the voltage window of 1.7–3.0 V. These two pairs of redox peaks are attributed to the reversible lithium-ion storage electrochemical behavior of the carbonyl group in PTO. Furthermore, the redox peaks within the 1.7–3.0 V range match the voltage range of lithium-sulfur batteries well. In contrast, no obvious redox peaks were observed in the carbon black modified separator. This indicates that the TTB-PTO-COF material can achieve reversible storage of lithium ions with four electrons within the voltage range of 1.7–3.0 V, i.e., it can form lithiation intermediates. Theoretically, these lithiation products can achieve redox catalytic functions similar to those of PTO lithiation products.

[0048] Example 5 The experiment of assembling Li || Li symmetric cells using TTB-PTO-COF material-modified separators and control group carbon black-modified separators included the following steps: In a glove box, CR2032 button cell cases were used, with lithium foil for both positive and negative electrodes. Modified separator materials were used for the separators. 40 µL of electrolyte was used to modify the separator materials with COF@2500 and CB@2500. Li || Li symmetric cells were assembled, and the effect of the modification layer on the lithium deposition / stripping behavior was reflected by the polarization voltage.

[0049] Appendix Figure 5 For Li || Li symmetric cells in the range of 0.2–1 mA cm⁻¹ -2 At current densities of 2-8 mA cm⁻¹, the polarization voltages of symmetrical cells assembled with the two membrane modification materials showed no significant difference; however, at current densities of 2-8 mA cm⁻¹, the polarization voltages were significantly different. -2 At current densities of 8 mA cm⁻¹, COF@2500 exhibits a lower polarization voltage than CB@2500, even at 8 mA cm⁻¹. -2 At high current densities, the polarization voltage of the COF@2500 assembled battery did not increase significantly. These results indicate that TTB-PTO-COF, due to its ordered pore size and multi-carbonyl structure, can effectively modulate the polarization voltage of Li. + The flux of ions promotes rapid deposition / stripping of lithium ions, thereby inhibiting the growth of lithium dendrites and reducing the risk of short circuits.

[0050] Example 6 The preparation of sulfur cathode materials includes the following steps: Preparation of sulfur composite material (KB / S): 25 mg Ketjenblack (KB) and 75 mg S8 were mixed and ground in a mortar for 30 minutes. The mixture was then transferred to ampoules, flame-sealed under argon atmosphere, and finally maintained in a tube furnace at 160°C for 12 hours. After the reaction was complete, the mixture was cooled to room temperature to obtain KB / S. Preparation of lithium-sulfur battery cathode: 70 mg KB / S, 20 mg Ketjenblack, and 10 mg binder (PVDF) were weighed and ground for 60 minutes. 0.5 mL of NMP solvent was added to prepare a slurry, which was then ground for another 30 minutes. This slurry was then coated onto carbon-coated aluminum foil to prepare a sulfur cathode. The cathode was dried in a vacuum oven at 60°C for 12 hours. For routine electrochemical testing, the sulfur loading was 1–1.2 mg·cm⁻¹. -2 By increasing the thickness of the doctor blade coating, a cathode with a high sulfur loading (4-6 mg·cm⁻¹) was prepared. -2 ).

[0051] Example 7 The modified membrane material is used in the assembly of lithium-sulfur batteries: In a glove box, a CR2032 coin cell case was used. The positive electrode was the one prepared in Example 7, the negative electrode was lithium foil, and the separator was a modified separator material. 40 µL of electrolyte (1 M LiTFSI dissolved in a mixed solvent of DOL and DME (volume ratio 1:1) with 0.1 M LiNO3 added) was used. During battery assembly, the side of the modified separator containing the active material was in contact with the sulfur positive electrode, and the blank side was in contact with the lithium negative electrode. The electrochemical testing window was 1.7–3.0 V vs Li / Li. + .

[0052] Performance testing: Cyclic stability testing, cyclic voltammetry testing, and electrochemical impedance spectroscopy (EIS) testing were performed on the button cell obtained in Example 7, which included the modified separator material.

[0053] Cyclic voltammetry (CV) test: Cyclic voltammetry (CV) curves were tested in the voltage range of 1.7 to 3.0 V, with a scan rate of 0.1 mV / s.

[0054] AC impedance (EIS) test: frequency set from 0.05Hz to 100kHz; Cyclic stability test: The Blue Electric test system was used, with a voltage test range of 1.1V-3.0V and a current density of 2C.

[0055] Among them, the half-cell assembled with COF@2500 and CB@2500 modified separators achieved a performance of 0.1 mV s. -1 The cyclic voltammetry curve is as follows Figure 6aAs shown, in the CV curve of the battery assembled with TTB-PTO-COF modified separator material, two reduction peaks appear at 2.27 V and 2.02 V, which are attributed to the transformation from S8 to long-chain Li2S, respectively. n (4 ≤ n ≤ 8) and Li2S n The conversion to Li₂S / Li₂S₂. At 2.34 V and 2.39 V, the two oxidation peaks correspond to the conversion of Li₂S / Li₂S₂ to Li₂S. n The conversion of the ions and the subsequent conversion to S8. Furthermore, compared to carbon black-modified membrane batteries, TTB-PTO-COF-modified membrane batteries exhibit higher peak currents and lower polarization voltages in both oxidation and reduction phases, indicating that TTB-PTO-COF-modified membrane batteries possess faster reaction kinetics.

[0056] The charge-discharge curves of half-cells assembled with COF@2500 and CB@2500 modified separators at 0.2C are shown below. Figure 6b As shown, the specific capacity of the half-cell assembled with COF@2500 is 1043 mA hg. -1 It is higher than the half-cell discharge capacity of the BC@2500 assembly (930 mAh g). -1 The half-cell assembled with COF@2500 exhibits a lower polarization voltage. This indicates that the TTB-PTO-COF modified membrane material can improve the utilization rate and conversion kinetics of active sulfur.

[0057] The EIS curves of half-cells assembled with COF@2500 modified separators are as follows: Figure 6c As shown, the batteries assembled with COF@2500 separator modification exhibited low Rct impedance and Warburg impedance during charge and discharge.

[0058] The long-cycle curves of half-cells assembled with COF@2500 and CB@2500 modified separators at 2C current density are shown below. Figure 6d As shown, the initial capacity of the half-cell assembled with COF@2500 is 766 mA hg. -1 The capacity is 501 mAh g after 500 cycles. -1 The capacity retention rate was 65.4%, and the capacity decay per cycle was only 0.069%, while the initial capacity of the lithium-sulfur battery assembled with CB@2500 was 723 mAhg. -1 After 500 cycles, the capacity is 309 mA hg. -1 The capacity retention rate was 42.7%, and the capacity decay per cycle was 0.114%, further demonstrating that the TTB-PTO-COF material-modified separator can improve the cycle stability of lithium-sulfur batteries.

[0059] The cycling curves of high-sulfur surface-loaded half-cells assembled with COF@2500 and CB@2500 modified separators at 0.1C are shown below. Figure 6e As shown, the COF@2500 membrane-modified battery has a discharge capacity of 889 mA hg at a 0.1 C rate. -1 The half-cell discharge capacity of the CB@2500 modified separator material assembly is 519 mA hg. -1 The comparative results show that the TTB-PTO-COF modified membrane material can effectively catalyze the conversion of LiPS to Li2S / Li2S2, improving the utilization rate of active materials. After 100 cycles, the capacity of the COF@2500 assembled battery is 774 mA hg. -1 The capacity retention rate was 87.0%, while the capacity of CB@2500 did not show a significant increase, indicating that BTT-PTO-COF can improve the utilization of active sulfur in high-load electrode materials.

[0060] In summary, the invention includes, but is not limited to, the above embodiments. Any equivalent substitutions or partial improvements made under the spirit and principles of this invention shall be considered to be within the protection scope of this invention.

Claims

1. A macroporous pyrenetetrone-triazine covalent organic framework material, characterized in that: The material has the following basic structural units: 。 2. The macroporous pyrenetetrone-triazine covalent organic framework material as described in claim 1, characterized in that: The material has an ordered crystalline structure and a specific surface area of ​​200~400 m². 2 / g, with a pore size of 3.5~4nm.

3. A method for preparing the macroporous pyrene-tetraone-triazine covalent organic framework material according to claim 1 or 2, characterized in that: The method steps include: Under a protective gas atmosphere, 2,7-aminopyrene-4,5,9,10-tetraone and 4,4',4''-(1,3,5-triazine-2,4,6-triyl)tri(benzaldehyde) were polymerized via a Schiff base reaction to obtain macroporous pyrene-tetraone-triazine covalent organic framework materials.

4. The method for preparing a macroporous pyrene-tetraone-triazine covalent organic framework material as described in claim 3, characterized in that: Under a protective gas atmosphere, 2,7-aminopyrene-4,5,9,10-tetraone, 4,4',4''-(1,3,5-triazine-2,4,6-triyl)tri(benzaldehyde) were mixed with solvent and catalyst. The mixture was flash-frozen with circulating liquid nitrogen, pumped out and thawed, and reacted in a closed reaction vessel at 80~150℃ for more than 24 hours. After the reaction was completed, the mixture was filtered, washed, purified and dried to obtain macroporous pyrene-tetraone-triazine covalent organic framework material.

5. The method for preparing a macroporous pyrene-tetraone-triazine covalent organic framework material as described in claim 4, characterized in that: The molar ratio of 2,7-aminopyrene-4,5,9,10-tetraone and 4,4',4''-(1,3,5-triazine-2,4,6-triyl)tris(benzaldehyde) is 3~4:2; And / or, the solvent includes one or more of N,N-dimethylacetamide, N,N-dimethylformamide, mesitylene, and 1,4-dioxane; And / or, the catalyst includes acetic acid, hydrochloric acid, and trifluoroacetic acid; And / or, the reaction temperature is 100~120℃, and the reaction time is 24~120h.

6. The application of the macroporous pyrene-tetraone-triazine covalent organic framework material as described in claim 1 or 2 as a modifying material in the preparation of modified lithium-sulfur battery separators.

7. The application as described in claim 6, characterized in that: A slurry is prepared by uniformly mixing the macroporous pyrene-tetraone-triazine covalent organic framework material, a conductive agent, and a binder. The slurry is then coated onto a separator and dried to obtain a modified lithium-sulfur battery separator.

8. The application as described in claim 7, characterized in that: The thickness of the modifying material is 1~20 µm.

9. The application as described in claim 7, characterized in that: The mass ratio of the macroporous pyrene-tetraone-triazine covalent organic framework material, the conductive agent, and the binder is 5:4:1 to 8:1:

1. The conductive agent includes carbon black, Ketjen black, acetylene black, and carbon nanotubes; the binder includes polyvinylidene fluoride, sodium alginate, PEDOT, and polydopamine; and the separator includes Celgard 2320, Celgard 2325, Celgard 2400, Celgard 2500, and Celgard 2501.

10. A lithium-sulfur battery, characterized in that: The battery separator is the modified lithium-sulfur battery separator as described in claim 6, with the modification material located on the positive electrode side.